2017
DOI: 10.1016/j.jtcvs.2017.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal esophageal trachealization and esophagocarinoplasty in the treatment of flow-limited Floyd II tracheal agenesis

Abstract: Floyd II tracheal agenesis with fistula (arrow) and after esophagocarinoplasty (right). Central Message Tracheal agenesis survival requires regional relationships, an innovative multidisciplinary approach, and family-centered care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Those few patients who survive postnatally require the presence of a functioning TEF that allows lifesaving esophageal intubation, followed by prompt distal esophageal occlusion and gastric decompression to allow for efficient ventilation. Subsequently, distal esophagostomy and esophageal neotrachealization or reconstruction is required [3,13,24,26]. Tazuke et al, in 2015, described four patients with TA with long-term survival (77-109 months) after airway and esophageal reconstruction [13].…”
Section: Discussionmentioning
confidence: 99%
“…Those few patients who survive postnatally require the presence of a functioning TEF that allows lifesaving esophageal intubation, followed by prompt distal esophageal occlusion and gastric decompression to allow for efficient ventilation. Subsequently, distal esophagostomy and esophageal neotrachealization or reconstruction is required [3,13,24,26]. Tazuke et al, in 2015, described four patients with TA with long-term survival (77-109 months) after airway and esophageal reconstruction [13].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al in 2015 reported survival up to almost 1 year for a type 2 TA while in the same year Tazuke et al reported survival ranging from 77 to 109 months for four children (two type 1, one type 2, one type 3) 15 16. Recently, Densmore et al reported survival (follow-up 146 days) in type 2 TA with neonatal trachealisation and oesophago-carinoplasty 17. Overall neo trachealisation of the oesophagus has been the surgery of choice; however, the outcomes still remain dismal for this rare condition.…”
Section: Discussionmentioning
confidence: 99%
“…Options in the future include tissue engineering offering a hope towards tracheal transplantation. Translational research and animal experiments may offer directions to a possibility of an ideal tracheal replacement with required rigidity, humidification, ciliary function and options of growth with the child 17. Till then TA remains a potentially lethal condition which can be a major burden to any healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…This type of tracheal agenesis and its surgical management is the subject of the case report in this issue of the Journal by Densmore and colleagues. 3 Salvage treatment of a critically ill neonate with tracheal agenesis is contingent on the presence of a tracheoesophageal or bronchoesophageal fistula, which allows esophageal intubation and mechanical ventilation. Prenatal diagnosis is rare and only suspected in the absence of a tracheoesophageal fistula.…”
mentioning
confidence: 99%
“…In 4 survivors reported from Osaka University, gastrointestinal continuity was established by gastric or jejunal interposition. 5 Densmore and colleagues 3 have modified this surgical approach to save a particularly high-risk patient who had a nearly atretic tracheoesophageal fistula and concerns for neurologic insult from postnatal hypoxia. Their report speaks to the coordinated effort required of multiple medical specialists, and the resources required at a tertiary care facility, to achieve a truly remarkable outcome for the patient and family.…”
mentioning
confidence: 99%